Anaerobic microsites have an unaccounted role in soil carbon stabilization - Marco Keiluweit (Nature Portfolio, 2017)
Mechanisms controlling soil carbon storage and feedbacks to the climate system remain poorly constrained. Here, the authors show that anaerobic microsites stabilize soil carbon by shifting microbial metabolism to less efficient anaerobic respiration and protecting reduced organic compounds from decomposition.